2018
DOI: 10.5194/hess-22-1509-2018
|View full text |Cite
|
Sign up to set email alerts
|

Calibrating electromagnetic induction conductivities with time-domain reflectometry measurements

Abstract: Abstract. This paper deals with the issue of monitoring the spatial distribution of bulk electrical conductivity, σ b , in the soil root zone by using electromagnetic induction (EMI) sensors under different water and salinity conditions. To deduce the actual distribution of depth-specific σ b from EMI apparent electrical conductivity (EC a ) measurements, we inverted the data by using a regularized 1-D inversion procedure designed to manage nonlinear multiple EMI-depth responses. The inversion technique is bas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 65 publications
(79 reference statements)
1
22
0
Order By: Relevance
“…ECa depends on the soil profile distribution of water electrical conductivity, σ w , volumetric water content, θ, tortuosity, τ, of the soil pore system, as well as on other factors related to the solid phase such as bulk density, clay content and mineralogy. Consequently, separating the effect of single soil properties (e.g., soil water) on ECa is no simple task (see for example, [17,18]). However, in two separate studies, [19,20] found spatial variation in soil water stored within the top 0.5 and 1.7 m to be highly correlated with the spatial variation in ECa measured with EMI sensors.…”
Section: Evaluating Model Simulations By Direct Water Content Measurementioning
confidence: 99%
“…ECa depends on the soil profile distribution of water electrical conductivity, σ w , volumetric water content, θ, tortuosity, τ, of the soil pore system, as well as on other factors related to the solid phase such as bulk density, clay content and mineralogy. Consequently, separating the effect of single soil properties (e.g., soil water) on ECa is no simple task (see for example, [17,18]). However, in two separate studies, [19,20] found spatial variation in soil water stored within the top 0.5 and 1.7 m to be highly correlated with the spatial variation in ECa measured with EMI sensors.…”
Section: Evaluating Model Simulations By Direct Water Content Measurementioning
confidence: 99%
“…All these models are purely empirical and usually calibrated by means of simple linear regression (e.g., McKenzie et al, 1989), multiple linear regression (e.g., Díaz & Herrero, 1992) or geostatistical techniques (e.g., García‐Tomillo et al, 2017). There are also consolidated mathematical techniques for the calculation of soil σ b values from EMI measurements (Zhdanov, 2018), which have been compared to TDR‐measured σ b values (Dragonetti et al, 2018). In this work, however, a semi‐empirical model was developed to predict, not the basic properties, but the EMI measurements themselves, specifically, the EM38 measurements at the two dipole orientations and various heights over the ground on the basis of the main five soil properties, besides temperature, on which soil conductivity depends at various depths.…”
Section: Discussionmentioning
confidence: 99%
“…The calibrations have been developed mostly under laboratory conditions using sandy soils [22,33,34]. Besides, some comparisons between different techniques for σ b measurement have been carried out, e.g., ER vs. TDR [22], TDR vs. FDR [35], ER vs. FDR [21], and EMI vs. TDR [18,36]. However, a comparison between more than two techniques, such as ER, EMI, and FDR, and for the appraisal of soil salinity in a large agricultural irrigated area of diverse soil texture has not been done up to date to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 99%